IMPACTS OF NON-INTEREST INCOME ON RISKS AND PROFITABILITY IN VIETNAM’S COMMERCIAL BANKS - Nguyễn Minh Sáng; Nguyễn Thị Thùy Trang (Tạp chí Khoa học Đại học Đà Lạt)
Using accounting data from 26 Vietnamese commercial banks over the period from 2008 to 2016, this article applies the panel data analysis method to investigate the impacts of non-interest income on risks and profitability for Vietnam banking industry. Research results indicate that non-interest activities of Vietnamese commercial banks increase the profitability, but do not impact on the risks. Based on the results of this study, some recommendations related to policies are given to enhance the operational efficiency of Vietnam’s commercial banking system.